Temporal aggregation in first order cointegrated vector autoregressive - Lisbeth Funding la Cour; Anders Milhøj (Copenhagen Business School (CBS), Department of Economics, 2006)
We study aggregation - or sample frequencies - of time series, e.g. aggregation from weekly to monthly or quarterly time series. Aggregation usually gives shorter time series but spurious phenomena, in e.g. daily observations, can on the other hand be avoided. An important issue is the effect of aggregation on the adjustment coefficient in cointegrated systems. We study only first order vector autoregressive processes for n dimensional time series Xt, and we illustrate the theory by a two dimensional and a four dimensional model for prices of various grades of gasoline.
hdl:10398/7605
Keywords: G10; 330